THE EFFECT OF AQUATIC TRAINING ON EXPLOSIVE STRENGTH AND THE ACCURACY OF THE SIDE THROW AND PENALTY KICK SKILLS IN YOUTH FOOTBALL PLAYERS - Asst. Prof. Dr. Abdullah Mohammed Tayawi (Scholars Digest Publishing, 2025)
Chapter One includes the introduction and significance of the research. Sports training is considered the foundation for developing players toward optimal performance. Aquatic training, as a part of athletic training, has a high impact on player performance. Football, being a team sport, requires multifaceted training. Accordingly, the significance of this study emerges from implementing aquatic training due to observed deficiencies in explosive strength and certain skills among the players of the Al-Alam Sports Club. Through the researcher’s observation of players during several competitions, it became clear that there is a need for such training to enhance player performance. The aim of the research was to identify the effect of aquatic training on explosive strength and the accuracy of the side throw and penalty kick skills among youth football players. The hypothesis of the study was that aquatic training would have a statistically significant positive effect on these variables. The researcher employed the experimental method using two groups (experimental and control). The research population consisted of players from Al-Alam Sports Club, totaling thirty players. The sample was divided into two groups of eleven players each. The most important conclusion drawn was that aquatic training had a positive effect on explosive strength and the accuracy of the side throw and penalty kick in the research sample. The researcher recommends applying this type of training in both team and individual sports and on different samples.
Keywords: Aquatic Training, Explosive Strength, Skill Accuracy, Youth Football Players, Penalty Kick and Side Throw.